1997
DOI: 10.1111/j.1600-0765.1997.tb01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory roles of adhesive interactions between lymphocytes and gingival fibroblasts

Abstract: Chronic adult periodontitis is usually characterized by inflammatory cell accumulation in the extravascular periodontal connective tissue. In order to reveal how the lymphocyte migration and retention in periodontal lesions is regulated, we have focused on the molecular basis for the adhesive interactions between lymphocytes and human gingival fibroblasts (HGF). In this study, we investigated the involvement of cell adhesion molecules in adhesive interactions between lymphocytes and HGF. We found that activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 10 publications
2
28
0
4
Order By: Relevance
“…A mAb OS/37, which is specific for a HA-binding epitope on CD44, was utilized to examine the possible involvement of CD44/HA interaction in T-lymphocyte-HGF adherence. It was found that OS/37 inhibited the binding of T-lymphocytes to HGF, while treatment of HGF with hyaluronidase likewise abrogated the binding in a dose-dependent manner (Murakami et al, 1996b(Murakami et al, , 1997. These results suggest that the CD44/HA pathway also participates in T-lymphocyte-HGF adherence.…”
Section: (3) Interaction With Endothelial Cellsmentioning
confidence: 56%
See 3 more Smart Citations
“…A mAb OS/37, which is specific for a HA-binding epitope on CD44, was utilized to examine the possible involvement of CD44/HA interaction in T-lymphocyte-HGF adherence. It was found that OS/37 inhibited the binding of T-lymphocytes to HGF, while treatment of HGF with hyaluronidase likewise abrogated the binding in a dose-dependent manner (Murakami et al, 1996b(Murakami et al, , 1997. These results suggest that the CD44/HA pathway also participates in T-lymphocyte-HGF adherence.…”
Section: (3) Interaction With Endothelial Cellsmentioning
confidence: 56%
“…This raised the possibility that the adhesive interactions may provide a certain intracellular signal and mutually affect each cellular function through the adhesive interactions As has been described above, it was demonstrated that IFN-ystimulated fibroblasts can function as APC under specific conditions by physically interacting with T-lymphocytes (Geppert and Lipsky, 1985;Maurer et al, 1985Maurer et al, , 1987Pober et al, 1983;Shimabukuro et at., 1996). On the other hand, it was also observed that the IFN-y-stimulated HGF suppressed the primary proliferative responses induced by mitogen or allo-APC and that the suppression was also caused by a direct adherence of T-lymphocytes to IFN-ystimulated HGF (Shimabukuro et al, 1992) (Murakami et al, 1996a(Murakami et al, , 1997 (Wilson et ca1., 1994). The fact that ICE mRNA expression was also detected in both resting and cytokine-activated HGF (Murakami et al, 1997) have an ability to produce the mature form of IL-IP.…”
Section: Physiological and Pathophysiological Roles Of Adhesive Intermentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that leukocytes interact directly with cardiac fibroblasts. Indeed, there are several examples in the literature of interactions between leukocytes and fibroblasts of different origins [5][6][7][8][9][10][11][12][13][14][15]. These interactions appear to modulate the level of subsequent fibrosis and might also affect the degree of inflammation in those tissues.…”
Section: Introductionmentioning
confidence: 99%